The impact of the COVID-19 pandemic on HIV testing in Peru: an interrupted time series analysis from 2014 to 2022 - Robinson A. Yrene-Cubas; Jesus Perez-Castilla; Daniel E. Reynaga-Cottle; Maria José Bringas; David R. Soriano-Moreno; Daniel Fernandez-Guzman; Jose A. Gonzales-Zamora (BMC Infectious Diseases)
Abstract Objectives Our objective was to evaluate the impact of COVID-19 on the proportion of past-year HIV testing in Peru. Methods Utilizing data from the National Demographic and Health Survey of Peru from 2014 to 2022, we conducted an interrupted time series analysis. The proportion of past-year HIV testing per quarter of each year was considered our unit of analysis. Statistical analysis involved segmented regression with Newey-West standard errors, dividing each year of evaluation into four quarters. Additionally, we applied an Autoregressive Integrated Moving Average (ARIMA) model. Results We included 211,359 participants aged 15 to 49 years. The proportion of past-year HIV testing in Peru showed a mean decrease of 8.33% (95%CI: -10.73% to -5.93%) after the COVID-19 lockdown (from August-2020) compared to the previous period (before March-2020). Prior to lockdown, there was a mean quarterly increase of 0.30% (95%CI: 0.21–0.40%) in testing proportion, while after the lockdown, there was a mean quarterly decrease of -0.24% (95%CI: -0.56–0.09%). HIV testing declined in 23 of the 25 regions, ranging from − 23.7% to -3.0%, except in Amazonas and Cajamarca, where increases of 5.3% and 6.8% were observed. Predictions of counterfactual values without the pandemic using the ARIMA model revealed a percentage drop of -9.20% (95%CI: -13.70 to -4.80) in observed compared to predicted values. Conclusions This study highlights the decrease in proportion of past-year HIV testing in Peru following the COVID-19 lockdown, emphasizing the urgent need for targeted interventions to address disparities and ensure equitable access to testing services.